Safety and immunogenicity of intramuscular, single-dose V590 (rVSV-SARS-CoV-2 Vaccine) in healthy adults: Results from a phase 1 randomised, double-blind, placebo-controlled, dose-ranging trial - Jonathan A. Robbins; Dereck Tait; Qinlei Huang; Sheri Dubey; Tami Crumley; Josee Cote; Julie Luk; Jeffrey R. Sachs; Kathryn Rutkowski; Harriet Park; Robert Schwab; William Joseph Howitt; et al. (EBioMedicine, 2022)
Summary: Background: Vaccines against COVID-19 are needed to overcome challenges associated with mitigating the global pandemic. We report the safety and immunogenicity of V590, a live recombinant vesicular stomatitis virus-based COVID-19 vaccine candidate. Methods: In this placebo-controlled, double-blind, three-part phase 1 study, healthy adults were randomised to receive a single intramuscular dose of vaccine or placebo. In Part 1, younger (18–54 years) and, in Part 2, older (≥55 years) adults seronegative for SARS-CoV-2 nucleocapsid received one of four V590 dose levels (5.00 × 105; 2.40 × 106; 1.15 × 107; or 5.55 × 107 plaque-forming units [pfu]) or placebo. In Part 3, a single V590 dose level (5.55 × 10⁷ pfu) or placebo was administered to younger SARS-CoV-2 seropositive adults. Primary endpoints included adverse events (AEs) and for Parts 1 and 2 anti-SARS-CoV-2 serum neutralising antibody responses measured by 50% plaque reduction neutralisation (PRNT50) assay at Day 28. Registration NCT04569786 [P001-02]. Findings: 232 participants were randomised and 219 completed the study. In seronegative participants, anti-SARS-CoV-2 spike-specific antibody responses to V590 were low and comparable to placebo across the lower dose levels. At the highest dose level (5.55 × 107 pfu), anti-SARS-CoV-2 spike-specific PRNT50 was 2.3-fold higher than placebo. The most frequently reported AEs were injection-site pain (38.4%), headache (15.1%) and fatigue (13.4%). Interpretation: V590 was generally well-tolerated. However, Day 28 anti-SARS-Cov-2 spike-specific antibody responses in seronegative participants following a single intramuscular administration of V590 were not sufficient to warrant continued development. Funding: The study was funded by Merck Sharp & Dohme LLC., a subsidiary of Merck & Co., Inc., Rahway, NJ, USA.